Multi-objective optimization and multi-criteria decision-making methods for optimal design of standalone photovoltaic system: a comprehensive review - Mohammed Ridha, Hussein; Gomes, Chandima; Hizam, Hashim; Ahmadipour, Masoud; Heidari, Ali Asghar; Huiling, Chen (Elsevier, 2021)
Standalone photovoltaic (SAPV) systems have been considered as promising and fast development renewable energy sources due to free-noise, easy availability, and low-cost, especially for remote areas. However, the main disadvantages of these systems are low energy conversion and high capital cost. Therefore, many factors should be considered before installing the SAPV systems such as types of PV panels and configurations, mathematical models of PV module, storage battery, environmental criteria, sizing method based on techno-economic objectives, and selection the final optimum configuration. The goals of this paper are to presents a comprehensive review of the recent development in designing SAPV systems based on multi-objective optimization (MOO) and multi-criteria decision-making (MCDM) methodologies, including the mathematical models used in estimating the output power of the PV module and storage battery are also presented. Finally, the techno-economic criteria for assessing the performance of the SAPV system are considered. This will help the designers and customers to choose the most suitable design before installing the SAPV system.